An unexpected Lewis acid catalyzed Diels-Alder cycloaddition of aryl allenes and acrylates. Issue 26 (30th June 2016) - Conner, Michael L.; Brown, M. Kevin
Abstract: An unexpected [4+2] cycloaddition of aryl allenes and simple acrylate derivatives is reported. This process functions well with a variety of allenes and acrylates to generate bi- and tricyclic dihydronaphthalene derivatives through a nonconventional bond disconnection. Graphical abstract: